A PRE-EXPERIMENTAL STUDY ON TEACHING ENGLISH VOCABULARY THROUGH SCRABBLE GAME TO THE TENTH GRADE STUDENTS OF SMK NEGERI 1 SENGAH TEMILA IN ACADEMIC YEAR 2018/2019 - Swi King, Liem (ENGLISH JOURNAL, 2020)
The researcher intends to use the scrabble game in teaching English at SMK Negeri 1 Sengah Temila and it is hoped this teaching can help to increase their vocabulary English easier. This case also attracts the researcher’s attention to conduct a research because the research that has been conducted to investigate this issue was not much enough especially in the Teachers’ Training and Education Faculty at Tanjungpura University. The purpose of this research is to investigate how high is the tenth grade students of SMK Negeri 1 Sengah Temila’s achievement in vocabulary taught by using scrabble game in the academic year 2018/2019. The measurement technique was applied for collecting the data and the descriptive method is used to describe the data. 39 students of class X a and X b out of 70 students (population) were taken as samples. The analysis displays that the average score of the students’ achievement vocabulary taught by using scrabble game is 65.95 in the post-test, 19.61 higher than the one in the pre-test (45.95). The obtained t-value is 11,65, higher than the t-table value, 2.00 (19.61>2.00), indicating that the difference is significant. The figures show that teaching vocabulary by using scrabble game to the tenth grade students of SMK Negeri 1 Sengah Temila in academic year 2018/2019 increased the students’ vocabulary achievement.